The human person in science and theology - Gregersen, Niels Henrik; Drees, Willen B.; Görman, Ulf (Issues in science and theology, 2000)
pt. 1. Towards a bio-cultural paradigm of personhood -- pt. 2. Supervenience, mind and culture.